2020
DOI: 10.1371/journal.pone.0228104
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of heat shock proteins and antioxidant enzymes in response to temperature, starvation, and parasitism in the Carob moth larvae, Ectomyelois ceratoniae (Lepidoptera: Pyralidae)

Abstract: Insects face diverse biotic and abiotic stresses that can affect their survival. Many of these stressors impact cellular metabolism, often resulting in increased accumulation of reactive oxygen species (ROS). Consequently, insects will respond to these stressors by increasing antioxidant activity and increased production of heat shock proteins (HSPs). In this study, the effect of heat, cold, starvation, and parasitism by Habroacon hebetor wasps was examined in the carob moth, Ectomyelois ceratoniae, to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 46 publications
3
24
0
Order By: Relevance
“…Hsp 90 gene expression was not significantly affected by the envenomation. Similar effects of both heat shock proteins were observed from the Carob moth larvae (Ectomyelois ceratoniae) on the first and second day after envenomation by H. hebetor (Farahani et al, 2020). Thus, we can speculate about manageable necrotic-like death (necroptosis) in the fat body cells of G. mellonella larvae under the influence of the venom components of H. brevicornis.…”
Section: Discussionsupporting
confidence: 69%
“…Hsp 90 gene expression was not significantly affected by the envenomation. Similar effects of both heat shock proteins were observed from the Carob moth larvae (Ectomyelois ceratoniae) on the first and second day after envenomation by H. hebetor (Farahani et al, 2020). Thus, we can speculate about manageable necrotic-like death (necroptosis) in the fat body cells of G. mellonella larvae under the influence of the venom components of H. brevicornis.…”
Section: Discussionsupporting
confidence: 69%
“…As typical stress response indicators, genes potentially encoding heat shock proteins and cytochrome P450s were differentially expressed, being partly up-and partly downregulated in A. rosae in response to starvation. Regulation of heat shock proteins in response to starvation has been reported elsewhere, including larvae of Lepidoptera and Hymenoptera (Farahani et al 2020;Wang et al 2012). These proteins act to stabilize and protect other proteins in the face of both abiotic and biotic stresses (Sørensen et al 2003;Farahani et al 2020).…”
Section: Discussionmentioning
confidence: 82%
“…Regulation of heat shock proteins in response to starvation has been reported elsewhere, including larvae of Lepidoptera and Hymenoptera (Farahani et al 2020;Wang et al 2012). These proteins act to stabilize and protect other proteins in the face of both abiotic and biotic stresses (Sørensen et al 2003;Farahani et al 2020). Cytochrome P450s are best known for their role in metabolism of xenobiotics by insects (Feyereisen 2012).…”
Section: Discussionmentioning
confidence: 96%
“…A few studies have revealed the requirement for molecular chaperones in diapause maintenance (MacRae, 2010) and starvation (Farahani et al, 2020). Elevated levels of chaperones inhibit stress-related, irreversible protein denaturation, and apoptosis (MacRae, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of chaperones inhibit stress‐related, irreversible protein denaturation, and apoptosis (MacRae, 2010). Hibernation‐ or starvation‐induced upregulation has been reported for genes encoding HSPs (Farahani et al, 2020; Hand et al, 2016; Li et al, 2007; Ren et al, 2016; Rinehart et al, 2007; G. Zhang et al, 2018); however, the response of other groups of chaperone genes to diapause or starvation is not known.…”
Section: Introductionmentioning
confidence: 99%